(27x+3+10x-2)/2=9x-5

Simple and best practice solution for (27x+3+10x-2)/2=9x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (27x+3+10x-2)/2=9x-5 equation:



(27x+3+10x-2)/2=9x-5
We move all terms to the left:
(27x+3+10x-2)/2-(9x-5)=0
We add all the numbers together, and all the variables
(37x+1)/2-(9x-5)=0
We get rid of parentheses
(37x+1)/2-9x+5=0
We multiply all the terms by the denominator
(37x+1)-9x*2+5*2=0
We add all the numbers together, and all the variables
(37x+1)-9x*2+10=0
Wy multiply elements
(37x+1)-18x+10=0
We get rid of parentheses
37x-18x+1+10=0
We add all the numbers together, and all the variables
19x+11=0
We move all terms containing x to the left, all other terms to the right
19x=-11
x=-11/19
x=-11/19

You can always share this solution

See similar equations:

| -12+x11=0 | | 9x+11-7x-5=-20 | | 7x-11-4x+8=18 | | 0.5x=300 | | 4/8+2/5=4/7x | | 0.8y=73 | | 3-7x=18+3x+5 | | t=4.25t=4.25 | | 15+7x=2x^2 | | (27x+3+9x-5)/2=10x-2 | | (6p+16)=7 | | 1x-54=25 | | 2x-11=9-3x | | 7/2xQ=1 | | 3?92? b=31? b?7 | | 5/8Xa=1 | | 1/6x————=5/2 | | -12x=-15x+-36 | | (Z=4)19-2z | | 2x+7x+x=180° | | 8n^2+8n-576=0 | | 4x+21+4x=3x-14 | | -(-9x+1)=10 | | -2x-2=34 | | 7y+2=5y+26 | | V=12x11/3 | | -y+12-2y=2 | | -5x+23=13 | | 8.6=2.1?1.3y | | 3x-3=-84 | | 6-4•n=12 |

Equations solver categories